Regional Government Responsibility Related to Disaster Mitigation through Human Rights-Based Spatial Policies in Palu City - Ismeti, Ismeti; Palipadang, Lembang; Tavip, Moh.; Weri, Asmadi (International Journal of Disaster Management, 2022)
The 2018 earthquake in Palu highlighted the city's vulnerability. For this reason, disaster mitigation efforts were needed to reduce the impact of disaster. Disaster mitigation can take the form of formulating human rights-based spatial policies. The government is obliged to protect, respect, and promote human rights. The rights that must be protected in the formulation of spatial planning policies are the right to information, the right to participate, and the right to justice. This study aims to determine why disaster mitigation efforts through spatial planning policies are important for local governments to undertake and what form the responsibility of local governments in disaster mitigation efforts through human rights-based spatial planning policies in Palu City takes. This study used qualitative research methods. The data obtained comes from primary and secondary sources. Primary data includes excerpts from interviews with stakeholders and observations, as well as laws and regulations. Secondary data include scientific articles published in various accredited national journals and reports from relevant state agencies and institutions. The results of this study found that mitigation through spatial planning policies based on human rights is important to be done because, in addition to reducing the impact of disaster, it also ensures that people's rights are not violated. Through this spatial planning policy, the community can identify potential threats of disaster to their residential areas, allowing them to make informed decisions about their future quality of life in that area. Furthermore, active community participation in the implementation of this policy is encouraged to reduce the impact of future disasters. It is hoped that other regions, especially those prone to disaster, can also apply the concept of disaster mitigation through human rights-based spatial planning policies based on the results of this research.